1977
DOI: 10.1172/jci108758
|View full text |Cite
|
Sign up to set email alerts
|

Prostaglandin biosynthesis by rabbit renomedullary interstitial cells in tissue culture. Stimulation by angiotensin II, bradykinin, and arginine vasopressin.

Abstract: A B S T R A C T Rabbit renomedullary interstitial cells were isolated and grown in tissue culture. These cells synthesize 0.8 ng ofprostaglandin E2 (PGE2) per microgram cellular protein per hour in monolayer tissue culture; prostaglandins A2 and F2x (PGA2 and PGF2c) biosynthesis was 10 and 5% of PGE2 biosynthesis, respectively. Arachidonic acid markedly stimulated the production of PGE2 and PGFax, with conversion rates of 0.24 and 0.02%o/h, respectively. Angiotensin II, hyperosmolality, bradykinin, and argi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
117
1
1

Year Published

1980
1980
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 335 publications
(125 citation statements)
references
References 43 publications
6
117
1
1
Order By: Relevance
“…In the medulla prostaglandins are also formed in the interstitial cells (Bohman, 1977;Zusman & Keiser, 1977) and two prostaglandin synthetases with differing pH optima have been isolated from medullary homogenates (Raz & Schwartzman, 1976). In the renal cortex prostaglandin synthesis is probably confined to arteriolar endothelial cells, although staining to cyclo-oxygenase antibodies has also been shown in the epithelial cells of Bowman's capsule in the rabbit and glomerular mesangial cells in the cow.…”
Section: Discussionmentioning
confidence: 99%
“…In the medulla prostaglandins are also formed in the interstitial cells (Bohman, 1977;Zusman & Keiser, 1977) and two prostaglandin synthetases with differing pH optima have been isolated from medullary homogenates (Raz & Schwartzman, 1976). In the renal cortex prostaglandin synthesis is probably confined to arteriolar endothelial cells, although staining to cyclo-oxygenase antibodies has also been shown in the epithelial cells of Bowman's capsule in the rabbit and glomerular mesangial cells in the cow.…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that perfusion of the renal medulla is sensitive to COX inhibition (110,113,119). Furthermore, renomedullary interstitial cells have receptors for ANG II and BK and release PGE 2 in response to these agents (21, 72,178,179,186). Recently, Qi et al (127) have shown that the COX-2 isoform is expressed in those cells and is responsible for this action.…”
Section: Medullary Po2 and Perfusion Of The Medullamentioning
confidence: 99%
“…Both AVP and ANG II stimulate renal synthesis of prostaglandins (PG) in vivo and in vitro (7)(8)(9). Rat glomerular epithelial and mesangial cells in culture pro- ' Abbreviations used in this paper: ANG II, angiotensin II; AVP, arginine vasopressin; d(CH2)5VDAVP, [1-(,-mer-capto-#0-cyclopentamethylene propionic acid)-4-valine, 8-D-arginine] vasopressin; dDAVP, 1-desamino-8-D-arginine vasopressin; DMSO, dimethyl sulfoxide; GFR, glomerular filtration rate; Kf, ultrafiltration coefficient; 6kPGFI., 6-keto-prostaglandin Fla; PG, prostaglandin(s), with the corresponding letter (E, F) for each series; SNGFR, single nephron GFR; TXB2, thromboxane B2.…”
Section: Introductionmentioning
confidence: 99%